Neuroprotective Effect and Possible Mechanisms of Berberine in Diabetes-Related Cognitive Impairment: A Systematic Review and Meta-Analysis of Animal Studies - Hao, Yanwei; Li, Jiaxin; Yue, Shengnan; Wang, Shaofeng; Hu, Shuangyuan; Li, Bin (Frontiers in Pharmacology, 2022)
Berberine, the main bioactive component of Coptis chinensis, is widely used in the treatment for diabetes. Previous studies have reported that berberine supplementation may play a multitarget therapeutic role in diabetes-related cognitive impairment (DCI). This systematic review and meta-analysis evaluated the effect and possible mechanisms of berberine in animal models of DCI. Relevant studies were searched through PubMed, Web of Science, Embase, and three Chinese databases, CNKI, Wanfang and VIP up to March 2022. Twenty studies including 442 animals were included and SYRCLE’s risk of bias tool was used to assess methodological quality. The statistical analysis was performed using STATA 15.0 to calculate weighted standard mean difference (SMD) with 95% confidence interval (CI). The fasting blood glucose (FBG) and Morris water maze test (MWM) were the main outcomes to be analyzed. The overall results showed that berberine could significantly improve FBG, escape latency, the times of crossing the platform, time spent in the target quadrant, serum insulin, 2hBG of oral glucose tolerance test (OGTT), amyloid β (Aβ), acetylcholinesterase (AchE), oxidative stress and inflammation levels. Present meta-analysis demonstrated that berberine could not only lower blood glucose levels but also improve learning and memory in DCI animal models, which might involve regulating glucose and lipid metabolism, improving insulin resistance, anti-oxidation, anti-neuroinflammation, inhibiting endoplasmic reticulum (ER) stress and improving cholinergic system. However, additional attention should be paid to these outcomes due to the significant heterogeneity.